Jesus and Muhammad: Their Prophetic Brotherhood and Commonality of Mission - A Muslim Perspective - Rahman, A. Faizur (The ecumenical review, 2020)
This essay foregrounds the reformatory teachings of two of the greatest men that walked the earth - Jesus and Muhammad. The majority of the followers of these honoured prophets attribute their success to the power and influence of their transcultural theologies and see them as nothing more than founders of independent religions. Another presumption is that their religions are mutually exclusive. This essay looks beyond creedal orthodoxies and inflexible articles of faith to find commonalities in the approaches of prophets Jesus and Muhammad while exploring the possibility of imagining their missions as liberatory responses to the socio-political conditions that prevailed during their times.